1993
DOI: 10.1007/bf00979664
|View full text |Cite
|
Sign up to set email alerts
|

Variability of terpene content in the soft coralSinularia flexibilis (Coelenterata: Octocorallia), and its ecological implications

Abstract: Colonies of the soft coralSinularia flexibilis (Quoy & Gaimard) (Coelenterata, Octocorallia) were collected at Lizard Island (14°40'S and 145°28'E) Research Station. Extraction of the corals and quantitative chemical analysis for the three major diterpene components, flexibilide, dihydroflexibilide, and sinulariolide, afforded average ratios of 4∶3∶1 respectively. Colonies, sized on the basis of the sterile stalk circumference, were analyzed for possible correlations between size and chemical composition. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 16 publications
1
31
1
Order By: Relevance
“…Most studies have focused on algae, gorgonians, and soft corals , Paul & Van Alstyne 1988, Harvell & Fenical 1989, Meyer & Paul 1992, Harvell et al 1993, Maida et al 1993, Yates & Peck01 1993, Cronin & Hay 1996. Sponges produce a large number of unique natural products (Faulkner 1997 and previous reviews).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies have focused on algae, gorgonians, and soft corals , Paul & Van Alstyne 1988, Harvell & Fenical 1989, Meyer & Paul 1992, Harvell et al 1993, Maida et al 1993, Yates & Peck01 1993, Cronin & Hay 1996. Sponges produce a large number of unique natural products (Faulkner 1997 and previous reviews).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on intraspecific chemical variation are valuable for understanding the factors affecting the production of chemical defenses, as well as providing insights into the ecological consequences and evolutionary implications of such variation. Intraspecific patterns of variation have been reported over temporal , betweencolony (Maida et al 1993, or within-colony (Paul & Van Alstyne 1988, Harvell & Fenical 1989, Van Alstyne et al 1994 scales. Although other functions cannot be ruled out, most data available support a n antipredatorv role of secondary metabolites (Paul 1992) and point to predation as one of the factors affecting intraspecific variation (Hay 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Concentrations and types of secondary metabolites have been reported to vary based on colony size, 297 depth, 273 ' 298 and proximity to competitors. 299 Site specific differences suggest that terpene levels may be influenced by environmental conditions.…”
mentioning
confidence: 99%
“…299 Site specific differences suggest that terpene levels may be influenced by environmental conditions. 297 ' 300 Crude extract concentrations vary among different parts of colonies, and some parts of soft coral or gorgonian colonies may rely more upon chemical defense while others rely more on structural defense. 35 ' 261 ' 301 " 302 Natural assemblages of coral reef fishes were deterred by extracts from three species of the Pacific alcyonacean Sinularia at the higher concentrations found in the polyp-bearing tissues at the top of colonies, while feeding was not affected by the lower concentration in the bottom portion of the colony.…”
mentioning
confidence: 99%
“…However, fewer examples described intra-specific geographical metabolite differences in coral. Maida et al [47] reported significant differences in flexibilide and sinulariolide metabolites of the soft coral Sinularia flexibilis among different sites at Lizard Island, Great Barrier Reef (Australia). Metabolite concentrations varied among the gorgonian coral Briareum asbestimum from different depths and geographical locations [48].…”
Section: Hypothesis 1: Paragorgia Arborea From Various Geographic Regmentioning
confidence: 99%